Pelaksanaan Zakat Pemilik Perkebunan Kelapa Sawit Di Desa Srimulyo Kecamatan Tungkal Jaya Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Desi Lauran Tinni; Ambok Pangiuk; Kurniati Kurniati (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This skripsi is motivated by the implementation of zakat for oil palm plantation owners in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province, whose practice is not in accordance with Islamic regulations. The aim of this research is: To find out the implementation of zakat on oil palm plantations in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province, to find out the understanding of the community in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province regarding zakat on oil palm plantations, to find out obstacles in implementing zakat on oil palm plantations in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra. This type of research is field research that uses qualitative descriptive methods. This research was carried out in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province, with a normative and sociological approach, using primary and secondary data sources. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data collection, data reduction, data presentation, then drawing conclusions. The results of the research show that the implementation of zakat for oil palm plantation owners in Srimulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province has quite large zakat potential. However, this was not implemented because there were various obstacles in its implementation, such as: oil palm plantation owners did not pay zakat because they lacked socialization about palm oil zakat, there was a lack of zakat amil institutions in socializing about zakat on oil palm plantations, some of them paid zakat as sincerely as they could. , not regularly paying zakat, assets that should be paid once a year. In fact, the amount of zakat they pay from oil palm plantations should be 2.5%, once a year, of total income. Oil palm plantation owners who are reluctant to pay zakat due to a lack of trust in zakat amil institutions, there are also those who have no intention of paying zakat at all.